PENDDIDIKAN THE PURE THEORY OF LAW: HANS KELSEN DALAM BIDANG ILMU HUKUM - Abdul Hijar Anwar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The growth of various schools of thought in legal theory shows a continuous struggle of thought in the field of legal science. If in the past, legal philosophy was a by-product of philosophers, today this position is no longer the case because legal philosophy issues have become separate material for study by jurists. The law of postivism for Hans Kelsen is that it must be cleaned of non-juridical elements, such as sociological, political, historical, even ethical elements. This thought is known as pure legal theory. For him law is a necessity that regulates human behavior as a rational being. In Indonesia, law has a very broad scope, not limited to the textual form of laws and regulations. In the functioning of law in the midst of society, it does not only require laws but other things such as community culture, law enforcement officials and facilities and infrastructure. From this we can see that the flow of positivism seeks to imprison law only textually.Keywords: The Pure Theory, Law, Hans Kelsen.